CHALCONE DYEING ON SILK FABRICS PRETREATED WITH CHITOSAN:OPTIMIZATION, ISOTHERM AND KINETICS - Riskiono Slamet (Program Studi Kimia Universitas Negeri Jakarta, 2017)
Surface response methodology was involved in the optimization of chalcone adsorption upon silk fabrics treated with chitosan against the process parameters pH, temperature and contact time. The effects of these factors were studied in the ranges 4.0-6.0 , 85-950C and 20-60 min at initial concentration chalcone dye 500 mg.Lâˆ’1, respectively. A predictive quadratic model was constructed by variance analysis of data obtained from a total of 20 experimental runs with three replicates each. The maximum q 279 mg/g was found under the experimental conditions of pH= 5.0, contact time = 40 and temperature = 90.Out of Langmuir isotherm models, adsorption data was best described by Langmuir isotherm with 0.99 consistency. The process kinetics was evaluated by pseudo-second order. Pseudo-second order kinetic model exhibited the highest correlation with data. The results showed that both monolayer adsorption and intra-particle diffusion mechanisms limited the rate of chalcone adsorption. Keywords:Chalcone, silk fabrics , optimization, kinetics and isotherm